Search Methods and Outcomes in Developing Countries: The Case of Venezuela - Gustavo Márquez; Cristobal Ruiz-Tagle (Inter-American Development Bank, Research Department, 2004)
This paper uses a newly developed panel data set for Venezuela in the period between 1994 and 2002 to analyze three basic questions. the first relates to the influence of personal characteristics and previous labor market experience in the choice of different search methods. The second question addresses the effectiveness of different search methods in moving out of unemployment, controlling for personal characteristics and previous job characteristics. Finally, the third questionpoints to the issue of former labor status by analyzing the relative weight of search method and previous job status in the determination of the likelihood of landing a job or dropping out of the labor force. We conclude that previous job status is a primary determinant of success in moving to employment, and that the use of employment agencies increases the likelihood of that move within each labor status.
Keywords: 330; Arbeitsuche; Arbeitslosigkeit; Venezuela